Measuring and modelling mechanochemical reaction kinetics. Issue 56 (19th June 2020) - Boscoboinik, Alejandro; Olson, Dustin; Adams, Heather; Hopper, Nicholas; Tysoe, Wilfred T.
Abstract : Quasi-static quantum calculations of the mechanochemical decomposition rate of methyl thiolate species on Cu(100) accurately reproduce the experimental kinetics measured in ultrahigh vacuum by an atomic force microscopy tip. Abstract : Quasi-static density functional theory calculations of the rate of mechanochemical decomposition of methyl thiolate species adsorbed on Cu(100) accurately reproduce the experimental normal-stress dependent rates measured in ultrahigh vacuum by an atomic force microscopy tip. This allows precise analytical models for mechanochemical reaction kinetics to be developed.